HORMONE EXAMINATION IN MENOPAUSE - Ferdy Royland Marpaung; Trieva Verawaty Butarbutar; Sidarti Soehita (Indonesian Association of Clinical Pathologist and Medical laboratory, 2019)
World Health Organization (WHO) and Stages of Reproductive Aging Workshop (STRAW) define menopause as a permanent end point of menstrual cycle that occurs naturally or by induction of surgical procedure, chemotherapy, or radiation. Clinically, menopause involved women over 40 or 50 years old. Approximately, fifty million women in the world is experiencing menopause annually. The etiology of menopause is classified into physiologic and non-physiologic. Pathophysiology of menopause includes decline of ovary function in menopause, response to loss of ovarian feedback mechanism, decline of hypothalamus and pituitary function. Endocrine changes in menopause lead to alteration of gonadotropin secretion cycle patterns, changes in steroid and peptide hormones through monophasic patterns to increase gonadotropin, decrease of estrogen, progesterone and inhibin. Clinical symptoms of menopause or estrogen deficiency syndrome classified into short term clinical symptoms and long term clinical symptoms. Hormonal examination in menopause consist of Follicular Stimulating Hormone (FSH), Anti-Mullerian Hormone (AMH), Luteinizing Hormone (LH), Inhibin B and Estradiol. The important of time to examine the hormones should be considered carefully.